AI Empowers Graphic Design Education: Innovation and Breakthrough - Wang, Yang; Cheng, Lijia; Lu, Fei; Zeng, Ailifei; Lu, Ling (LPPM STIKI Malang, 2024)
In the 1950s, the scientific community first proposed the term